Design and Build Electrical Gamelan as a Cultural Tourism Supporting Object - Erna Alimudin; Arif Sumardiono; Zaenurrohman Zaenurrohman; Saepul Rahmat; Riyani Prima Dewi; Hera Susanti (Urecol Journal. Part E: Engineering, 2021)
Widarapayung Wetan, Binangun District, Cilacap Regency is an innovation village entrusted by the Regional Planning, Development, Research and Development Agency (BAPPEDA) of Cilacap Regency to the Cilacap State Polytechnic. The current partner's problem is the difficulty in introducing cultural tourism to tourists visiting Widarapayung Wetan Village. One of the cultural tourism potentials in Widarapayung Wetan Village is a traditional Javanese musical instrument, namely the gamelan. Currently, gamelan cultural activities in Widarapayung Wetan Village have been actively carried out on a regular basis based on the existing schedule of activities. Therefore, in order for gamelan to become a unique attraction, it is combined with electronic technology to become an electric gamelan. The electric gamelan can be used by visitors freely to learn to play the gamelan, while the existing original gamelan can be well preserved for rehearsals and performances. The electric gamelan made are saron and demung instruments. The saron and demung blades use acrylic material. When the acrylic blade is hit/beaten with a hammer, the piezoelectric sensor will receive vibrations when the blade is hit. The vibrations will be converted into electrical energy. The electrical energy will go through the Zener diode and 1 M? resistor, and will enter into IC 4051. IC 4051 in the system functions as a multiplexer that will take only one input according to the tone of the saron or demung instrument blades that are hit. The input will be passed to Arduino for processing. Arduino will issue a sound output in the form of a tone according to the blade that is hit. The electric gamelan tone is the original tone recorded by the saron and demung instruments. The two electric gamelan instruments, saron and demung, were tested together with wiyaga and the head of the Padhang Bulan Widarapayung Wetan art studio. The next activity was socialization with members of the Padhang Bulan art studio and the village apparatus of Widarapayung Wetan.